The economy of England, 1450-1750 - Coleman, D. C. (London ; New York : Oxford University Press, 1977)
A study of the impact of the building trade on the northern economy before the industrial revolution.
Includes index.
Bibliography: p. [206]-215.
aia 26/9/2018
Loan
Keywords: Great Britain